Self-Explanation, An Instructional Strategy to Foster Clinical Reasoning in Medical Students - Martine Chamberland; Sílvia Mamede (Health Professions Education, 2015)
Clinical reasoning is a critical and complex skill that medical students have to develop in the course of their training. Although research on medical expertise has successfully examined the different components of that skill, designing educational interventions that support the development of clinical reasoning in students remains a challenge for medical educators. The theory of medical expertise describes how students׳ medical knowledge develops and is progressively restructured during their training and in particular through clinical exposure to patient problems. Instructional strategies to foster students’ learning from practice with clinical cases are scarce. This article describes the use of self-explanation as such a strategy. Self-explanation is an active learning technique of proven effectiveness in other domains which consists of having students explaining to themselves information on to-be-learned materials. The mechanisms through which self-explanation fosters learning are described. Self-explanation promotes knowledge development and revision of mental representations through elaboration on new information, organisation and integration of new knowledge into existing cognitive structures and monitoring of the learning process. Subsequently, the article shows how self-explanation has recently been investigated in medicine as an instructional strategy to support students׳ clinical reasoning. Available studies have demonstrated that students׳ diagnostic performance improves when they use self-explanation while solving clinical problems of a less familiar clinical topic. Unfamiliarity seems to trigger more self-explanations and to stimulate students to reactivate relevant biomedical knowledge, which could lead to the development of more coherent representations of diseases. The benefit of students׳ self-explanation is increased when it is combined with listening to residents׳ self-explanation examples and with prompts. The positive effect of self-explanation gets stronger when students׳ diagnostic performance is tested on far-transfer clinical cases, suggesting that deeper understanding and meaningful learning do occur. Self-explanation is a practical and inexpensive technique which could be incorporated into learning activities using clinical problems to promote diagnostic reasoning of medical students. Even though self-explanation is a promising learning technique, further studies are needed to explore other conditions that could maximise its benefit on learning clinical reasoning.